Ancient Damascus. A Historical Study of the Syrian City-State from Earliest Times until its Fall to the Assyrians 732 B.C.E. - Pitard, Wayne T. (1987)
’Āpum in the MBA. Upi during the LBA. Damascus and the monarchs of United Israel. Aram-Damascus from Rezon to the usurpation of Hazael. From the rise of Hazael to the fall of Damascus in 732 B.C.E.